Impact of virtual education on the student learning process - Núñez Esquivel, Gustavo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The incidences of virtuality in the learning process of students of the Faculty of Economic and Administrative Sciences of the National University of Itapúa (FACEA). The objective is to know the opinion of the students about virtual teaching. The population is the students of the FACEA. The quantitative approach of a sample of 153 students. The students consider that virtuality, under the given conditions, does not favor the learning of academic content. Men consider that virtuality favors the learning of academic content, however, women mostly think that it does not.